2021
DOI: 10.2106/jbjs.rvw.21.00045
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of 3 Treatment Arms for Vertebral Compression Fractures

Abstract: Background: Osteoporotic vertebral fractures (OVFs) have become increasingly common, and previous nonrandomized and randomized controlled trials (RCTs) have compared the effects of cement augmentation versus nonoperative management on the clinical outcome. This meta-analysis focuses on RCTs and the calculated differences between cement augmentation techniques and nonsurgical management in outcome (e.g., pain reduction, adjacent-level fractures, and quality of life [QOL]). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 67 publications
0
9
0
1
Order By: Relevance
“…8 These findings have subsequently been supported by several other studies and meta-analyses that show superior improvement in pain scores in patients treated with percutaneous cement augmentation versus conservative management, specifically in patients who have acute fractures with persistent and severe pain. 9-11 These studies have also shown similar outcomes in pain reduction when comparing PVP and PKP.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…8 These findings have subsequently been supported by several other studies and meta-analyses that show superior improvement in pain scores in patients treated with percutaneous cement augmentation versus conservative management, specifically in patients who have acute fractures with persistent and severe pain. 9-11 These studies have also shown similar outcomes in pain reduction when comparing PVP and PKP.…”
Section: Discussionmentioning
confidence: 65%
“…8 These findings have subsequently been supported by several other studies and meta-analyses that show superior improvement in pain scores in patients treated with percutaneous cement augmentation versus conservative management, specifically in patients who have acute fractures with persistent and severe pain. [9][10][11] These studies have also shown similar outcomes in pain reduction when comparing PVP and PKP. More recent studies looking at TIVAD have shown promising results compared with PKP, although there are currently limited data for the TIVAD procedure compared with classic cement augmentation procedures.…”
Section: Discussionmentioning
confidence: 65%
“…Most physicians and guidelines recommend a trial of conservative management with nonopioid analgesics and rehabilitative treatment before proceeding to invasive treatments. In fact, many interventional studies require that patients fail to achieve adequate pain relief and/or functional improvement from rehabilitative treatment prior to enrollment …”
mentioning
confidence: 70%
“…Although the present review asserts a lack of evidence to support interventional treatments, it does not account for the effectiveness of various treatments based on specific diagnoses. There are numerous high-quality studies that have demonstrated excellent clinical outcomes and cost-effectiveness when patients are properly diagnosed and treated accordingly …”
mentioning
confidence: 99%
“…In contrast, a systematic review and meta-analysis of 8 placebo- or sham-controlled RCTs of spinal cord stimulation compared with conventional therapy failed to show any clinically meaningful difference in a 10-point visual analog scale (VAS difference, 1.15; minimally important difference [MID], 1.4) . The second review compared vertebroplasty and kyphoplasty with nonoperative management in 12 trials, of which 4 were sham procedure controlled . These studies again failed to meet the MID of 1.4 on the 10-point VAS pain scale, in both the short term (VAS difference, 1.31) and long term (VAS difference, 0.9).…”
mentioning
confidence: 99%